2006
DOI: 10.1136/jnnp.2006.087726
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomised controlled trial of a home-based exercise programme aimed at improving endurance and function in adults with neuromuscular disorders

Abstract: Aim: To investigate the feasibility and effect of a home-based exercise programme on walking endurance, muscle strength, fatigue and function in people with neuromuscular disorders (NMDs). Methods: 20 adults with NMDs recruited to a control (n = 11) or exercise (n = 9) group were assessed by blinded assessors at baseline and at week 8. Walking and strengthening exercises were given to the exercise group in an 8-week home exercise programme. A 2-min walk distance was the main outcome measurement; isometric musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 13 publications
0
21
0
4
Order By: Relevance
“…The patient-specific aspect of this study, and the prescription of exercise on a low-intensity, high-frequency basis, allowed the investigator to gently overload each patient while targeting the muscles primarily affected by the disease. 19 The protocol was well tolerated by all the patients and did not cause adverse muscle symptoms or elevation of serum CK levels. From interviews with the patients, it was generally felt by those who had previously had exercise therapy that this had been too strenuous and had resulted in muscle pain and increased levels of weakness and fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient-specific aspect of this study, and the prescription of exercise on a low-intensity, high-frequency basis, allowed the investigator to gently overload each patient while targeting the muscles primarily affected by the disease. 19 The protocol was well tolerated by all the patients and did not cause adverse muscle symptoms or elevation of serum CK levels. From interviews with the patients, it was generally felt by those who had previously had exercise therapy that this had been too strenuous and had resulted in muscle pain and increased levels of weakness and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…22 Home-based programs are easy to implement, are accessible to the patient, and encourage compliance. 19 The impaired mobility that typifies a patient with IBM gives a home-based exercise program obvious advantages over a class-based program-in particular, the safety and familiarity of exercising in their own home, the assistance and encouragement of partners, the flexibility to perform the exercises according to their own schedule, and the avoidance of arranging transport.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rather than being reliant on continuous physiotherapy input, clients are motivated to share the commitment to their physical wellbeing [23]. More time educating on home exercise programmes, collaborative goal setting between specialist physiotherapists and their clients and guidance on such issues as fatigue management could, when appropriate, endow clients with strategies to assist them to achieve this [8,24,25]. Nevertheless, the extent and progression of the condition, leading to differing client needs, will necessitate variability in intervention and hence frequency of attendance [26].…”
Section: Patterns Of Utilizationmentioning
confidence: 98%
“…Physiotherapy may be important in order to maintain as much muscle function as possible, and help the patients to function at their highest level within the constraints imposed by the disorders. Previous studies have shown that exercise can improve muscle strength and endurance in persons with LGMD and FSHD (van der Kooi et al, 2004; Olsen et al, 2005; Dawes et al, 2006; Sveen et al, 2007). However, to the best of our knowledge, no study has examined whether specific physiotherapy approaches (such as the Bobath concept) may influence the gait pattern in these patients.…”
Section: Introductionmentioning
confidence: 98%